Spontaneous formation and closure of full thickness macular hole after treatment with anti-vascular endothelial growth factor therapy in polypoidal choroidal vasculopathy - Sethia, Abhishek (Indian J Ophthalmol, 2019)
Full-thickness macular hole (FTMH) formation in Polypoidal choroidal vasculopathy (PCV) after intravitreal anti-vascular endothelial growth factor (anti-VEGF) treatment is a rare complication. Spontaneous closure of FTMH following anti-VEGF therapy has not been described in PCV till date. We present a case of Asian woman with PCV who developed a FTMH following treatment with intra-vitreal anti-VEGF injections which subsequently closed spontaneously on further course of treatment.